Influence of Robotics Curriculum on Career Choices: an Exploratory Study with High School Students(*) - M. Selvam, Rejina (2019)
Career choices of high school students can be affected by a multitude of factors. Discerning these factors may facilitate parents, educators, and industries to know where students place most of their trust, and what criteria influence the career selection process. The current study was mainly concerned on the impact that technical studies, offered in high school, had on the selection of engineering studies in a group of girls. An exploratory study was conducted using data obtained from senior female students at La Vall High School, using surveys and school records from a period of 10 years. We attempted to identify up to what extent Math level and robotics programme had an influence on career choice, especially on choosing engineering studies. Our findings suggest the following: (1) the percentage of choosing Engineering as a career has incremented drastically post robotics programme offered at the school; (2) students’ interest in learning about the robotics programme positively influences choosing engineering as a career in spite of math level; (3) the study analyses the collected information and identifies existing trends in the career choice of engineering studies; (4) finally, the current exploratory study provides suggestions and explore implications and recommendations for future researchers and practitioners of institutions.